Proliferative Potential of Three Plantain Varieties In A Semi-Controlled Agro-Ecosystem At Gbado-Lite City (Nord Ubangi), Democratic Republic of the Congo - Jospin B. Gbelegbe; Jean B. Mokese; Jean-Bernard Z. Bosanza; Koto-Te-Nyiwa Jean-Paul Ngbolua (Britain International for Academic Research (BIAR) Publisher, 2023)
A study was conducted at Gbado-Lite city to assess the capacity of plantain macro-propagation by applying the PIF technique. To do this, the fragments of three types of banana trees: French, true horn and false horn were sown in a propagator containing sawdust. After germination, the seedlings were transplanted into polyethylene bags containing a mixture of clay and potting soil and installed under the shadehouse. With regard to the results obtained and statistical tests (at the 5% threshold), the significant difference between these three types of banana trees was only observed for the number of seedlings emitted by explant, the number of suckers weaned, the height of the plants at weaning and the mortality rate of plants in the nursery. Thus, emergence having taken place 2 weeks after sowing, after 46 days after resumption and 61 days after sowing, the French type was significantly different from two others with an average of 6 seedlings emitted and 4 suckers weaned per explant; the true and false horn being tied with 5 seedlings and 3 weaned suckers per explant. As for the height of the plants at weaning, the true horn (19.9 cm) was significantly higher than the other two (French: 17.7 cm and false horn: 19.6 cm). Finally, with 1.1% for True horn had a significantly lower mortality rate for plants in the nursery than the others (6.7% for French horn and 3.8 % for False horn). Although, the PIF technique influenced the suckering in a way strongly dependent on the cultivars, it can be popularized for these three types studied in order to promote banana cultivation in the agro-ecological conditions of Gbado-Lite.